Formation Of The Medieval Cities In The Kesh Oasis - Parmanov, Shokir (The journal of contemporary issues in business and government, 2021)
This article is devoted to the formation and development of medieval cities in an oasis called Kesh oasis in the medieval sources located in the eastern part of the Kashkadarya Oasis, one of the largest historical and cultural countries of Central Asia, in which the information on the formation and development of the first cities in this region during the first Iron Age As the main factor in the formation of cities in the territory, the passage of a network of the Great Silk Road from the Oasis territory was noted as one of the main factors. The author also elaborated on the basis of comparison, comparison, analysis of the names of about ten major cities of the Middle Ages in the Oasis and their location, the data presented in the written sources of the Middle Ages with the results of archaeological research conducted in recent years.